The History Learning Activities and Outcomes in Inquiry and Expository Learning Model: Do Both Make a Difference? - Jumaisa Jumaisa (Tarbawi : Jurnal Ilmu Pendidikan, 2021)
This research examines student learning activities and outcomes in the inquiry and expository learning model at SMA Negeri 14 Makassar. The research used the experimental design. The sample of this research was all students at the Class X IIS of SMA Negeri 14 Makassar. It consisted of two groups: students of Class X IIS2 as the experimental group and Class X IIS1 as the control group. The sample of this study was carried out using the Cluster Random Sampling technique. The data analysis technique used an independent sample t-test. The results found differences in the activities and learning outcomes of students' history taught using the inquiry and expository learning models. The activities and learning outcomes of the history of students taught by the inquiry learning model are better than those taught by the expository learning model.